Relationship Between Personality (Opennes, Conscientiousness, Extraversion, Agreeableness, Emotional Stability) With Student’s Environmental Moral Behavior - ULIS PRATIWI PURNAMA SARI (Universitas Negeri Jakarta, 2016)
This aim of this reseach is to find out the relationship between personality with student’s environmental moral behavior, personality consists of five factors (openess, conscietiousness, extraversion, agreeableness and emotional stability) which each of the factors will be sought the relationship with student’s environmental moral behavior. This research used quantitative with survey method, involved 120 samples in Bhineka Tunggal Ika Senior High School. Data were colleted through participant observation using the instrument with quesioner. Based on the empirical data as the results of this reseach, personality is important to improve student’s environtmental moral behavior, especially on openness, conscientiousness and emotional stability factors.